The Ottoman Administration of Iraq, 1890-1908 - Çetinsaya, Gökhan (SOAS/Routledge Studies on the Middle East, 2006)
This is a study of the nature of Ottoman administration under Sultan Abdulhamid and the effects of this on the three provinces that were to form the modern state of Iraq. The author provides a general commentary on the late Ottoman provincial administration and a comprehensive picture of the nature of its interaction with provincial society. In drawing on sources of the Ottoman archives, bringing together and analyzing an abundance of complex documents, this book is a fascinating contribution to the field of Middle Eastern studies.